Strategy for Strengthening Muhammadiyah Ideology and Doctrine - Nuryami Nuryami; Moh Nurhakim; Saiful Amien (Yayasan Letiges Konsultan Sosial, 2024)
Amid globalization and modernization, Muhammadiyah gradually needs to improve the strategy of understanding ideology and doctrine. This study aims to identify the strategies or steps Muhammadiyah took to enhance the understanding of ideology among its members or cadres, one of which is at the Ahmad Dahlan Institute campus in Probolinggo. This study is a qualitative case study and the method used is direct observation by the researcher to review the strategy for strengthening Muhammadiyah's ideology and doctrine. The results of the study indicate that the strategy implemented by Muhammadiyah to overcome this decline in understanding of ideology includes: First, regulating the recruitment pattern of academic staff members at the Ahmad Dahlan Institute Probolinggo campus (lecturers, staff, employees) with the approval of the Muhammadiyah leadership and the Daily Advisory Board who are fully committed to strengthening Muhammadiyah's identity. Second, through a cadre formation process integrating Islamic and Muhammadiyah courses for students, study activities for lecturers and staff, student discussions, routine activities such as Sunday morning studies, visits to lecturers and staff, and cultural da'wah activities in Probolinggo. This study needs to sufficiently explore the long-term impact of these strategies on Muhammadiyah's understanding of ideology. The originality of this study lies in its in-depth exploration of specific recruitment and cadre formation strategies in the Muhammadiyah academic environment, which provides unique insights into how Muhammadiyah identity is maintained and strengthened in the context of higher education.